Export of Labor Resources and Development of Human Capital in the Eurasian Integration - TOKSOBAEV, BULAT T.; NUKEEVA, MEDINA A.; TUGELBAEVA, DARYIKA M.; MANSUROVA, AIYMKAN CH.; TOKSOBAEVA, BAKTYGUL A. (The journal of contemporary issues in business and government, 2021)
The market transformations that have taken place in the Kyrgyz economy and the political crises over the past ten years have had a negative impact on the formation of labor and capital market structures. As a result, the Kyrgyz Republic becomes a “donor” of migrants, loses the most active part of the population, which leads to a deepening of socio-economic problems. The article considers the change in the average GDP growth in the EAEU countries over five years, the main indicators of the socio-economic development of the republic, the main indicators of the labor market, internal and external migration, and the structure of the disposable income of the population of the Kyrgyz Republic. The reasons are established and the economic-statistical system and comparative analysis and generalization of problems in the system of vocational education and in the labor market are carried out. This made it possible to identify and ultimately can have a positive impact on improving the socio-economic situation in the Kyrgyz Republic.